Defining the interconnectivity of the medial prefrontal cortex and ventral midbrain - Hui, May; Beier, Kevin T. (Frontiers in Molecular Neuroscience, 2022)
Dysfunction in dopamine (DA) signaling contributes to neurological disorders ranging from drug addiction and schizophrenia to depression and Parkinson Disease. How might impairment of one neurotransmitter come to effect these seemingly disparate diseases? One potential explanation is that unique populations of DA-releasing cells project to separate brain regions that contribute to different sets of behaviors. Though dopaminergic cells themselves are spatially restricted to the midbrain and constitute a relatively small proportion of all neurons, their projections influence many brain regions. DA is particularly critical for the activity and function of medial prefrontal cortical (mPFC) ensembles. The midbrain and mPFC exhibit reciprocal connectivity – the former innervates the mPFC, and in turn, the mPFC projects back to the midbrain. Viral mapping studies have helped elucidate the connectivity within and between these regions, which likely have broad implications for DA-dependent behaviors. In this review, we discuss advancements in our understanding of the connectivity between the mPFC and midbrain DA system, focusing primarily on rodent models.